Laser-driven low energy electron beams for single-shot ultra-fast probing of meso-scale materials and warm dense matter - Katerina Falk; Michal Šmíd; Karel Boháček; Uddhab Chaulagain; Yanjun Gu; Xiayun Pan; Pablo Perez-Martin; Miroslav Krůs; Michaela Kozlová (Scientific Reports, 2023)
Abstract Laser wakefield acceleration has proven to be an excellent source of electrons and X-rays suitable for ultra-fast probing of matter. These novel beams have demonstrated unprecedented spatial and temporal resolution allowing for new discoveries in material science and plasma physics. In particular, the study of dynamic processes such as non-thermal melt and lattice changes on femtosecond time-scales have paved a way to completely new scientific horizons. Here, we demonstrate the first single-shot electron radiography measurement using an femtosecond electron source based on the downramp-density gradient laser-wakefield-acceleration with the use of a compact Ti:sapphire laser. A quasi-monoenergetic electron beam with mean energy of 1.9 ± 0.4 MeV and charge 77 ± 47 pC per shot was generated by the laser incident onto a gas target and collimated using a two ring-magnet beam path. High quality electron radiography of solid objects with spatial resolution better than 150 $$\upmu$$ μ m was demonstrated. Further developments of this scheme have the potential to obtain single-shot ultrafast electron diffraction from dynamic lattices. This scheme poses a great promise for smaller scale university laboratories and facilities for efficient single-shot probing of warm dense matter, medical imaging and the study of dynamic processes in matter with broad application to inertial confinement fusion and meso-scale materials (mg g/cm $$^2$$ 2 ).